Identification of STRBP as a Novel JAK2 Fusion Partner Gene in a Young Adult With Philadelphia Chromosome-Like B-Lymphoblastic Leukemia - Zhang, Xin-Yue; Dai, Hai-Ping; Li, Zheng; Yin, Jia; Lang, Xing-Ping; Yang, Chun-Xiao; Xiao, Sheng; Zhu, Ming-Qing; Liu, Dan-Dan; Liu, Hong; Shen, Hong-Jie; Wu, De-Pei; et al. (Frontiers in Oncology, 2021)
Philadelphia chromosome-like B-lymphoblastic leukemia (Ph-like ALL) describes a group of genetically heterogeneous, Ph-negative entities with high relapse rates and poor prognoses. A Janus-kinase-2 (JAK2) rearrangement has been reported in approximately 7% of Ph-like ALL patients whose therapeutic responses to JAK inhibitors have been studied in clinical trials. Here, we report a novel STRBP-JAK2 fusion gene in a 21-year-old woman with Ph-like ALL. Although a normal karyotype was observed, a hitherto unreported JAK2 rearrangement was detected cytogenetically. STRBP-JAK2 fusion was identified by RNA sequencing and validated by Sanger sequencing. The Ph-like ALL proved refractory to traditional induction chemotherapy combined with ruxolitinib. The patient consented to infusion of autologous chimeric antigen receptor (CAR) T cells against both CD19 and CD22, which induced morphologic remission. Haplo-identical stem cell transplantation was then performed; however, she suffered relapse at just one month after transplantation. The patient subsequently received donor lymphocytes infusion after which she achieved and maintained a minimal residual disease negative remission. However, she succumbed to grade IV graft-versus-host disease 7 months post-transplant. In conclusion, this report describes a novel STRBP-JAK2 gene fusion in a Ph-like ALL patient with a very aggressive disease course, which proved resistant to chemotherapy combined with ruxolitinib but sensitive to immunotherapy. Our study suggests that CAR T-cell therapy may be a viable option for this type of leukemia.